أثر إستراتيجية التعلم البنائي الاجتماعي - حمي, سليم (جامعة الوادي University of Eloued, 2018)
هدفت هذه الدراسة للكشف عن أثر إستراتيجية التعلم البنائي الاجتماعي على اتجاهات تلاميذ السنة الثانية متوسطة نحو مادة الرياضيات بمتوسطة خليفة بن حسن بمدينة قمار ولاية الوادي، حيث تكونت عينة الدراسة من ( 35 ) تلميذا وتلميذة تم اختيارهم عشوائيا، من تلاميذ السنة الثانية متوسط للسنة الدراسية 2016/2017؛ حيث تم تدريسهم بإستراتيجية التعلم البنائي الاجتماعي، وتم استخدام استبانه الاتجاهات نحو مادة الرياضيات المعدة من طرف الباحث "عقيل بن ساسي" جامعة ورقلة، وقد أسفرت نتائج الدراسة إلى تحسن اتجاهات التلاميذ نحو مادة الرياضيات، مع وجود فروق ذات دلالة إحصائية في اتجاهات نحو مادة الرياضيات بين الجنسين لصالح الذكور .وكان من أهم الاقتراحات التي خرجت بها الدراسة أهمية تحسين اتجاهات الأساتذة والتلاميذ نحو مادة الرياضيات والمواد الدراسية. This study aimed to detect the impact of the strategy of social constructionist learning on attitudes towards Mathematics in second year middle school pupils in Khalifa Ben Hacen, Ghemar, city of El Oued. The study sample consisted of (35) male and female pupils were selected randomly, pupils in the second year of middle school for the academic year 2016/2017; where they were taught using strategy of social constructionist learning. Attitudes towards Mathematics questionnaire designed by the researcher Akil Ben Saci, University of Ouargla, was administered. The results of the study showed improvement in pupils' attitudes towards Mathematics, with statistically significant differences in attitudes toward Mathematics according to gender in favor of males .Amongst the most important suggestions of the study, was the importance of improving teachers and pupils' attitudes towards Mathematics and other study modules.
على اتجاهات تلاميذ السنة الثانية متوسط نحو مادة الرياضيات
مقال
Keywords: إستراتيجية التعلم البنائي الاجتماعي ؛ اتجاهات ؛ السنة الثانية متوسط ؛ الرياضيات; Social constructionist learning strategy; Attitudes towards Mathematics